COMPARACIÓN DE LA RELACIÓN DE LA PERCEPCIÓN DEL ESTILO DE VIDA EN SU DIMENSIÓN PERCEPCIÓN DE LA CONDICIÓN FÍSICA Y CONSUMO DE ALCOHOL EN PERSONAS CON DIABETES TIPO 2 Y SIN ELLA (JÓVENES EN LA CIENCIA, 2017)
Alcohol consumption in the world is the main risk factor for the development of more than 60 diseases responsible for approximately 4% of the total disease burden. The consumption of alcohol by diabetic patients makes the control and management of their disease is hampered, leading to worse controls, it is also an important factor for non-compliance and is one of the main causes of metabolic decompensation. The objective of the investigation was to analyze if there is a relation between the perception of the physical condition and the consumption of alcohol and the accomplishment of physical activity assuming that the accomplishment of physical activity diminishes the consumption of alcohol, nevertheless we find that there is not a relation Between both variables in people with type 2 diabetes and in children of those people.
Keywords: Array; Array; Array; Array